Non-porous interpenetrating Co-bpe MOF for colorimetric iodide sensing. Issue 38 (3rd September 2021) - Rani, Deepika; Bhasin, Kuldeep Kumar; Singh, Monika
Abstract : An interpenetrating non-porous ladder shaped MOF, Co- bpe, display remarkable solvatochromic iodide sensing through a double nucleophilic substitution mechanism. Abstract : MOFs with their accessible voids/channels have been explored immensely for sensing due to their exclusive host–guest chemistry. However, unavailability of pores/voids in interpenetrating non-porous MOFs limits their applications in sensing. We herein report for the first time, hitherto, a non-porous MOF with an interpenetrating ladder structure for iodide sensing. A Co- bpe MOF was synthesized by hydrothermal reaction between cobalt nitrate and 1, 2-bis(4-pyridyl)ethylene ( bpe ) in methanol and tested against colorimetric sensing of halides. The supramolecular structure of the Co- bpe MOF was stabilized through strong hydrogen bonding. We propose a double nucleophilic substitution reaction mechanism for iodide detection, which is one of its own kind. While Co- bpe showed a significant color change from dark maroon to dark green in the presence of iodide, the rest of halides did not display any pronounced colorimetric effect. The limit of detection (LOD) of this material was found to be 2.7 × 10 –7 M. This article focuses on the equal competency of non-porous MOF materials with the porous MOFs in sensing applications.